Range and timing of surgery, and surgical sequences used, in primary repair of complete unilateral cleft lip and palate: The Cleft Care UK study. (20th November 2019) - Slator, Rona; Perisanidou, Lydia Iyamu; Waylen, Andrea; Sandy, Jonathan; Ness, Andy; Wills, Andrew K.
Abstract: Objects: To describe the range of surgery used to repair the lip and palate in the UK with specific interest in the sequence/timing used in complete unilateral cleft lip and palate (cUCLP). Setting and Sample Population: The Cleft Care UK study, a cross‐sectional study of 268 5‐year‐olds, born from 2005 to 2007, with complete unilateral cleft lip and palate. Materials & Methods: Information on surgery was extracted from medical notes by surgeons during research clinics and transcribed onto a standardized questionnaire. Results: Surgical data were available for 251 (94%) children from all cleft centres in the UK (n = 18). Over a two‐year period, 32 surgeons used 10 different surgical sequences in primary repair of the cleft lip and palate. The most frequently used sequence was repair of cleft lip and anterior hard palate followed by repair of posterior hard palate and soft palate (70%). Four surgical sequences were used only once. Most surgeons had a preferred sequence, but 38% (11/29) used more than one sequence during the study period. The timing of repair of the lip, the hard palate and the soft palate varied with surgical sequence, and also between surgeons, even adjusting for the different sequences used. Conclusion: Despite centralization of cleft services in the UK, there remains considerable variation in both the sequence and timing of surgical repair of cleft lip and palate in infancy. Further work is required to understand whether these factors are associated with differences in outcome.